2020
DOI: 10.1155/2020/9345602
|View full text |Cite
|
Sign up to set email alerts
|

Brain Functional Network in Chronic Asymptomatic Carotid Artery Stenosis and Occlusion: Changes and Compensation

Abstract: Asymptomatic carotid artery stenosis (CAS) and occlusion (CAO) disrupt cerebral hemodynamics. There are few studies on the brain network changes and compensation associated with the progression from chronic CAS to CAO. In the current study, our goal is to improve the understanding of the specific abnormalities and compensatory phenomena associated with the functional connection in patients with CAS and CAO. In this prospective study, 27 patients with CAO, 29 patients with CAS, and 15 healthy controls matched f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…This study identified that patients with SACS exhibited altered pairwise CT co-vary patterns with increased interhemispheric but decreased intrahemispheric Manhattan distances seeding from the left lateral temporal regions. This result is consistent with prior reports on atrophy and dysconnectivity in the same regions (e.g., Cheng et al, 1970 ; Lin et al, 2014 ; Avelar et al, 2015 ; Marshall et al, 2017 ; Tani et al, 2018 ; Nickel et al, 2019 ; Gao et al, 2021b ), and also generally consistent with previous reports using fMRI functional connectivity or diffusion tensor imaging SC ( Lin et al, 2014 ; Huang et al, 2018 ; Gao et al, 2019 ; He et al, 2020 ). For example, earlier results from resting-state functional connectivity show that SACS has reduced interhemispheric connectivity, especially in the frontoparietal network ipsilateral to stenosis ( Cheng et al, 1970 ).…”
Section: Discussionsupporting
confidence: 93%
“…This study identified that patients with SACS exhibited altered pairwise CT co-vary patterns with increased interhemispheric but decreased intrahemispheric Manhattan distances seeding from the left lateral temporal regions. This result is consistent with prior reports on atrophy and dysconnectivity in the same regions (e.g., Cheng et al, 1970 ; Lin et al, 2014 ; Avelar et al, 2015 ; Marshall et al, 2017 ; Tani et al, 2018 ; Nickel et al, 2019 ; Gao et al, 2021b ), and also generally consistent with previous reports using fMRI functional connectivity or diffusion tensor imaging SC ( Lin et al, 2014 ; Huang et al, 2018 ; Gao et al, 2019 ; He et al, 2020 ). For example, earlier results from resting-state functional connectivity show that SACS has reduced interhemispheric connectivity, especially in the frontoparietal network ipsilateral to stenosis ( Cheng et al, 1970 ).…”
Section: Discussionsupporting
confidence: 93%
“…In our previous hemispheric network study, we found that the communication of CAS patients’ coordination and information on the affected side of the brain was significantly impaired, but the contralateral brain network has shown the brain network compensation effect. In the left cerebral hemisphere of patients with CAO and CAS of the right carotid artery, connections between the Rolandic operculum and insula, median cingulate and paracingulate gyri and postcentral gyrus, and superior parietal gyrus and precuneus were stronger than those in normal controls [ 20 ]. Therefore, the results suggest that patients with carotid artery stenosis have different effects on the affected side, and that hemispheric template results may be more accurate for the global analysis of graph theory.…”
Section: Discussionmentioning
confidence: 99%
“…Although the coverage was wide and high‐quality journals were included, work reported in non‐peer‐reviewed publications, conference papers, and in other languages was excluded. A few recent fMRI studies were excluded as they did not include a treatment (Chang et al., 2016 ; Goode et al., 2009 ; He et al., 2020 ; Liu et al., 2020 ; Porcu et al., 2020 ; Xiao et al., 2018 ), conduct both precognitive and postcognitive tests (Liu et al., 2020 ; Muscas et al., 2019 ; Xiao et al., 2018 ), or examine the internal carotid arteries (Rosen et al., 2018 ). Similarly, a couple of task‐phase fMRI studies that examined only motor recovery using a motor task without additional pre/postrevascularization cognitive evaluation were excluded (Jensen et al., 2008 ; Schaaf et al., 2010 ).…”
Section: Discussionmentioning
confidence: 99%